Network Indignation: Changes and Continuities in Juvenile Political Socialization From June 2013 (Global Journal of Human-Social Science, 1970)
The article presents results of comparative longitudinal investigations of youth political socialization between the years 2012 and 2015 having as reference the network movements of June 2013 in a city far from the major centers of political mobilization Analyzes are made about the relationship between the new organizational arrangements of social movements the insertion and growth of the use of social networks in the political and cultural mediation of youth with the political arena and its possible consequences on changes and continuities in the process of political socialization of teenagers and young people from public high school Through the application of a survey in the city of Cascavel State of Paran a gradual trend towards the paradigmatic opening of traditional social institutions in the social participation of young people was evidenced in line with the multimodal characteristics that encourage political participation through social networks
Keywords: network movements; youth; june 2013